Kiriku ja rahva ühiselt elamise kunst. Missioloogiline uurimus „Elust, usust ja usuelust 2020“ põhjal - Kurg, Ingmar (Usuteaduslik Ajakiri, 2024)
The art of living together as church and people. A Missiological Analysis Based on the ‘On Life, Faith, and Religious Life 2020’ Study The position of the church in contemporary society has been a constant focus of Estonian EUU research. It turns out that the church has supporters both within and outside the membership. Outside the church, the most positive attitudes are among the group of people who identify themselves as believers in God. This evidence has led to a key conclusion about the future focus of the church. It makes sense for the church to focus its attention and care on supporting people who believe in God. Missiologically, the importance of conviviality, i.e. the art of all parties in society living together, is well known. In this conviviality, i.e. the active communion of Church and people, is a guarantee of truthfulness as parrhesia, that is to say, speaking to one another openly and honestly,